REVIEW OF LEGAL CERTAINTY OF ROYALTY COLLECTION ON MUSIC AND/OR SONGS: A COMPARATIVE STUDY OF INDONESIA AND RUSSIA - Febrian, Muhammad Naufalurridho; Setyawati, Ria; Noventri, Ardhana; Mahendra, Yusril (Sabtida, 2025)
Copyright protection is one of the constitutional rights related to intellectual property, including copyrights on music and/or songs. Under the Copyright Law, royalties are recognized as compensation for the use of the economic rights of a creation. This study focuses on performing rights royalties, which require any person using songs and/or music for commercial purposes in public services to pay royalties to the creators through the National Collective Management Organization (LMKN). However, in practice, the collection of royalties remains problematic, particularly regarding the definition of